The Role of Extension Agents in Improving Livestock Productivity to Support Sustainable Livestock Development - Maria Alfonsa Ngaku; Agnes Yunita Dea; Varianus Teru (Jurnal Biologi Tropis, 2026)
Livestock extension workers play a key role in efforts to increase livestock productivity while ensuring sustainable livestock development. As catalysts for change, extension workers disseminate technological innovations, provide non-formal education, and provide technical assistance aimed at increasing the capacity of livestock farmers. The method used in this study was a literature study with qualitative descriptive analysis techniques through library research, which examined the role of livestock extension workers in increasing livestock productivity in support of sustainable livestock development. As a result of structured extension activities, extension workers help farmers implement efficient feed management, appropriate reproduction strategies, preventive animal health practices, and cultivation techniques that can improve the quality and quantity of livestock production. In addition to technical aspects, extension workers also play a role in strengthening farmer institutions, developing agribusiness partnership patterns, and improving business literacy so that farmers are able to compete in a more modern value chain. On the environmental side, extension workers encourage the implementation of environmentally friendly farming practices through waste management, resource conservation, energy efficiency, and the application of animal welfare standards that ensure the sustainability of the production ecosystem. Thus, the role of extension workers is not only focused on increasing productivity, but also on building a resilient, adaptive, and socially and ecologically responsible farming system. Overall, extension workers are the main drivers of livestock transformation towards sustainable development that can support food security, farmer welfare, and long-term sustainability of natural resources.